Gut microbiota shape B cell in health and disease settings. Issue 2 (11th May 2021) - Yu, Baichao; Wang, Luman; Chu, Yiwei
Abstract: Recent accumulating evidence supports the hypothesis that the intricate interaction between gut microbiota and the immune system profoundly affects health and disease in humans and mice. In this context, microbiota plays an important role in educating and shaping the host immune system which, in turn, regulates gut microbiota diversity and function to maintain homeostasis. Studies have demonstrated that intestinal microbiota participates in shaping B cells in health and disease settings. Herein, we review the recent progress in understanding how microbiota regulates B-cell development, focusing on early-life B-cell repertoire generation in GALT and how microbial products, including microbial antigens and metabolites, affect B-cell activation and differentiation to ultimately regulate B-cell function. We also discuss the interaction between gut microbiota and B cells under pathogenic conditions and highlight new approaches that can be applied to treat various diseases. Graphical Abstract: Review on gut microbiota and its impact on shaping the host B cells; which, in turn, regulates gut microbiota diversity and function.